2009
DOI: 10.1532/hsf98.20091045
|View full text |Cite
|
Sign up to set email alerts
|

Distal Leg Protection for Peripheral Cannulation in Minimally Invasive and Totally Endoscopic Cardiac Surgery

Abstract: The use of antegrade selective perfusion of the lower extremity at the side of peripheral cannulation for port-access perfusion and endoaortic occlusion is of utmost importance in patients undergoing minimally invasive or endoscopic cardiac surgery. NIRS monitoring has proved to be very helpful for the diagnosis of impaired leg perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…A prolonged period of limb ischemia in patients undergoing minimally invasive operations, especially when the femoral artery has been clamp occluded, has the potential to cause ischemic complications. 3 The use of NIRS to monitor the lower extremities in these patients was a valid and reproducible method for assessing tissue oxygenation of the perfused leg, immediately showing signs of leg ischemia if insufficient leg perfusion is provided. 4,5 According to our results, there was a significant drop of the tissue oxygenation (as decreased NIRS values) after femoral artery cannulation and CPB, which was found in direct correlation with the body weight of the patient.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A prolonged period of limb ischemia in patients undergoing minimally invasive operations, especially when the femoral artery has been clamp occluded, has the potential to cause ischemic complications. 3 The use of NIRS to monitor the lower extremities in these patients was a valid and reproducible method for assessing tissue oxygenation of the perfused leg, immediately showing signs of leg ischemia if insufficient leg perfusion is provided. 4,5 According to our results, there was a significant drop of the tissue oxygenation (as decreased NIRS values) after femoral artery cannulation and CPB, which was found in direct correlation with the body weight of the patient.…”
Section: Discussionmentioning
confidence: 94%
“…Regional oxygen saturation measured by means of nearinfrared spectroscopy (NIRS) have been used as potential surrogate of cerebral and somatic mixed venous oxygen saturation and has been suggested as a noninvasive tool to continuously monitor and detect states of low body perfusion. [1][2][3][4][5] We sought to evaluate the safety of peripheral arterial cannulation by using NIRS in patients undergoing minimally invasive heart surgery for correcting simple congenital heart diseases, focusing on patients with a body weight less than 30 kg.…”
mentioning
confidence: 99%
“…Using NIRS to continuously monitor blood flow, poor oxygenation due to inadequate perfusion can be treated immediately. 9) We also routinely use NIRS during MICS along with the ultrasonographic assessment. Toya et al 8) reported that relative changes from the baseline value were more useful than the absolute rSO 2 value evaluating intraoperative lower limb ischemia in MICS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to monitoring tissue oxygenation and blood flow, ensuring adequate distal perfusion after femoral cannulation is also important to prevent leg ischemia. Some reported methods of maintaining blood flow to the lower leg after femoral cannulation are inserting a downstream cannula, 3 , 9 , 10) suturing a side graft, 5 , 11) or using a bidirectional arterial cannula. 12) Bonaros et al 9) reported that minor or major complications of leg perfusion occurred in only 1.7% with routine use of selective distal leg perfusion before placing the arterial cannula.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation